2016
DOI: 10.1108/mf-08-2015-0221
|View full text |Cite
|
Sign up to set email alerts
|

Spillovers of international interest rate swap markets and stock market volatility

Abstract: Purpose The purpose of this paper is to investigate volatility spillovers across the interest rate swap markets of the G7 economies, and then the authors investigate whether spillovers of swap markets contain useful information to explain subsequent stock price movements. Design/methodology/approach This study uses the short- and long-term swap spread volatility of the G7 countries to explore the spillover effects of international swap markets, and then investigates the relationship between swap and stock ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…As diverse financial assets become increasingly interconnected, the study suggests that options for diversification are shrinking. The results align with the existing studies (Lee et al, 2016;Kakinuma, 2021). The results derived from the study may not be valid for other scenarios.…”
Section: Discussionsupporting
confidence: 73%
“…As diverse financial assets become increasingly interconnected, the study suggests that options for diversification are shrinking. The results align with the existing studies (Lee et al, 2016;Kakinuma, 2021). The results derived from the study may not be valid for other scenarios.…”
Section: Discussionsupporting
confidence: 73%
“…Dontis-Charitos et al (2013) examined return spillovers using a bivariate multivariate GARCH (MGARCH) model and revealed the presence of strong return spillovers from the FTSE to the banks but not vice versa. Similarly, Lee et al (2016) found a moderate spillover effect that spreads from short-to long-term swap markets. In a similar study, Yahchouchi (2014) found that in each market, there is the prevalence of volatility and significant volatility spillovers from small to relatively larger markets in Middle Eastern and North African stock markets.…”
Section: Introductionmentioning
confidence: 88%
“…However, as we indicate later the rolling-window framework has several severe limitations relative to the time-varying parameter method we are proposing. Very recently this strand of literature -analyzing interest rate, as well as bond yields, spillovers -has become quite popular, see for example, ; Galariotis et al (2018); Cronin (2014); Garcia-de Andoain and Kremer (2017); Berisha et al (2018); Sowmya et al (2016); Lee et al (2016).…”
Section: Introductionmentioning
confidence: 99%